Assessing Conceptual Understanding via Literacy-Infused, Inquiry-Based Science among Middle School English Learners and Economically-Challenged Students - Rafael Lara-Alecio; Beverly J. Irby; Fuhui Tong; Cindy Guerrero; Janice Koch; Kara L. Sutton-Jones (MDPI AG, 2018)
The overarching purpose of our study was to compare performances of treatment and control condition students who completed a literacy-infused, inquiry-based science intervention through sixth grade as measured by a big idea assessment tool which we refer to as the Big Ideas in Science Assessment (BISA). First, we determine the concurrent validity of the BISA; second, we investigate the differences in the post-test of the BISA between treatment and control English Learners (ELs), controlling for their performance in the pre-test; third, we analyze the differences in the post-test of the BISA between treatment and control non-ELs, controlling for their performance in the pre-test; and fourth, we examine the relationship between students' English language proficiency as measured by standardized assessment, and their performance in the BISA among ELs and non-ELs, respectively. Our findings indicate: (a) literacy-infused science lessons with big ideas, implemented through the tested intervention, improved students' language acquisition and science concept understanding for ELs and economically challenged students (ECs); (b) there was a positive relationship between language and content for both ELs and non-ELs, with a similar magnitude, suggesting that students with a higher level of English proficiency score higher in science assessment; and (c) the lesson plans prepared were successful for promoting a literacy-infused science curriculum via a 5E Model (Engage, Explore, Explain, Elaborate, and Evaluate) that includes three to five of the Es used daily. A pedagogical approach for a literacy-infused science model with big ideas is proposed.